K-State Turfgrass Research 2010 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2010)
Turfgrass Research 2010 contains results of projects conducted by Kansas State University faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day on Aug. 5, 2010, at the Rocky Ford Turfgrass Research Center in Manhattan, Kan. Articles in this Report of Progress summarize research projects that were completed recently or will be completed in the next year or two. Specifically, this year's report presents summaries of research on turf and the environment, pest control, and turf evaluations.
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-346-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1035; Turfgrass; Disease control; Weed control; Creeping Bentgrass; Evaluation; Zoysiagrass